Knowledge، attitudes and practices toward risk factors of hepatitis virus infection among Health practitioners - Khasbak, Ahmed Ali; Hassan, Salim Hussein; Ali, Jafar Khalaf (Journal of medical and pharmaceutical sciences, 2018)
Viral hepatitis is identify by epidemiological ability to infect many members of the community، hepatitis is one of the most common chronic infectious diseases worldwide، especially developing countries، and is one of the serious health problems in Iraq and neighboring countries. The study was designed to find out to assess the knowledge regarding symptoms، risk factors and prevention of hepatitis infection among a sample of Health and Medical practitioners. A cross – sectional study including (196) individuals were conducted at many hospitals and health centers at holy Karbala city during December 1 2017 to march 1 2018. Data were collected based on a pre-prepared questionnaire filled out by direct interview. The data were analyzed using the(spss) scientific statistical package (PSAW-18) after coding.The current study showed that 44% of the sample had good information about the disease. 29% of the sample had fair information about the disease and 27% of the sample had poor information about the disease.The current study concluded that less than half of the research sample possessed good information about the disease. there were a high significant different between gender and social status as compared to sample information. while there was no significant different between age group and academic achievement compared to sample information.
Keywords: hepatitis A type; knowledge; health personnel; hepatitis B type; hepatitis C type